Adalékok a Gömöri-medence történeti földrajzához - Frisnyák, Sándor (Közép-Európai Közlemények, 2012)
The Gömör Basin covers approximately the area of the historical Gömör and Kishont Counties. The Gömör Basin (like the interpretation of the Carpathian Basin) forms a single geographical unit together with the Carpathian Mountains and the water basins of the Sajó, Csetnek, Murány, Turóc, Balog and Rima. This kind of interpretation of the basin, the economic unity and complementarity of the two natural landforms, could be typical at the time of the organization of the Hungarian county system. The area of the historical Gömör County rose to 4279 km2 when Kishont (1802) and the Csermosnya Valley (1881) were added to its territory. The county lying in the basin is a perfect geographical unit comprising heterogeneous geological and geomorphological parts, the southern hills divided by river basins and the northern mountains. The mountains are made up of the Vepor and Slovak Ore Mountains. This short paper focuses on a relatively narrow research area of historical geography; the investigation of spatial and temporal aspects of changes in land use up till 1920 based on literature4review, cartographic and statistical sources and empirical studies.